2021
DOI: 10.1101/2021.03.08.432999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retention Time Prediction Using Neural Networks Increases Identifications in Crosslinking Mass Spectrometry

Abstract: Crosslinking mass spectrometry (Crosslinking MS) has developed into a robust technique that is increasingly used to investigate the interactomes of organelles and cells. However, the incomplete and noisy information in the spectra limits the numbers of protein-protein interactions (PPIs) that can be confidently identified. Here, we successfully leveraged chromatographic retention time (RT) information to aid the identification of crosslinked peptides from spectra. Our Siamese machine learning model xiRT achiev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…S6), indicating that self-CSMs are approaching exhaustive coverage at the given experimental detection limit. Similar results were seen when including retention time data of heteromeric and self-CSMs 20 .…”
Section: Comparison Of a Cleavable To A Non-cleavable Crosslinkersupporting
confidence: 81%
See 1 more Smart Citation
“…S6), indicating that self-CSMs are approaching exhaustive coverage at the given experimental detection limit. Similar results were seen when including retention time data of heteromeric and self-CSMs 20 .…”
Section: Comparison Of a Cleavable To A Non-cleavable Crosslinkersupporting
confidence: 81%
“…This bases on the assumption that not knowing the individual peptide masses before the search results in the need for exhaustive combination of all peptides in the database and thus an explosion of the search space. However, there are multiple large-scale studies that have successfully employed a non-cleavable crosslinker despite these assumptions 4,12,20,21 . These are based on a detailed understanding of how crosslinked peptides fragment 22 , that offered a computational solution to knowing the individual peptide masses which was then implemented in the search algorithm xiSEARCH 3 .…”
Section: Comparison Of a Cleavable To A Non-cleavable Crosslinkermentioning
confidence: 99%
“…35−37 We just noticed that a recent paper also used retention time prediction to increase identification of cross-linked peptides. 38 Herein, we found that the monolinked peptides carried out the information on the retention time of the corresponding cross-linked pairs, and the retention time of cross-linked peptides can be well predicted by the use of the retention time of the monolinked peptides. Unlike linear peptide prediction, the training data set and the test data set in this study can be generated from same LC-MS/ MS data set, which is more like internal calibration and will ensure that the prediction of cross-linked peptides is always accurate.…”
Section: ■ Introductionmentioning
confidence: 86%
“…By pulling the crosslinked peptide pairs from the background, significantly higher depth of analysis can be achieved. Further optimizations are currently being explored with, for example, extensive fractionation (Lenz et al, 2021), advanced MS setups (Steigenberger et al, 2020), tailored data acquisition approaches (Hauri et al, 2019;Giese et al, 2021), and more robust reporting in terms of false-positive identifications (Lenz et al, 2021). A combination of these modified reagents, technological advancements, and optimization of reagents' membrane permeability will undoubtedly further improve proteome-wide in situ crosslinking results.…”
Section: System-wide In Situ Xl-ms and Its Limitationsmentioning
confidence: 99%